Investigating the impact of implementation ISO 9000 on Inventory of Supply Chain - Reza Baradaran Kazemzadeh (مدیریت مهندسی و رایانش نرم)
اISO 9000 is an international quality management standard that introduced as key criteria for assessing suppliers, a possibility for international trade, and a requirement for government bids in many countries. Moreover, implementing this standard positively affected processes and internal communication in supply chain organizations. Inventory also plays an important role in cost management in supply chains. It seems that the implementation of this standard could improve inventory indexes in the supply chains. In this paper, 39 companies in the stock market of Iran were used to assess by two indexes of inventory return and inventory to working capital to recognize the effects of ISO 9000 on the supply chain. Results indicated that ISO 9000 had no positive effect on inventory turnover and just caused some minor improvement on inventory to capital turnover in the investigated companies.